Biodistribuição do pertecnetato de sódio (Na99mTcO4) em ratos submetidos à ressecção extensa de intestino delgado - Chacon, Dâmaso de Araújo (2007)
Massive resection of the small intestine results in short bowel syndrome with anti-absorptive effect and repercussions on the metabolism. Morphologic and functional evaluation may be necessary in order to control wrapped organs. Scintigraphy an examination with little invading and no biologic damage can be used. The purpose were to assess the biodistribution of sodium pertecnetate in organs of rats subjected to massive resection of the small intestine, the intestinal adaptation of the remnant intestinal mucosa and weight curve evaluation in the postoperative period. Twenty-one Wistar rats were randomly allocated into three groups (n = 7). The operated group named short bowel (SB) after anesthetized was subjected to massive resection of the small intestine; the control group (C), and sham group (SHAM). On the 30th postoperative day, 0.l mL of sodium pertechnetate was injected into the venous orbital plexus. After 30 minutes, the rats were killed with an overdose of anesthetic, and fragments of the liver, spleen, pancreas, stomach, duodenum, small intestine, thyroid, lung, heart, kidney, bladder, muscle, femur and brain were harvested. The percentage of radioactivity per gram of tissue (%ATI/g) was determined using Gama Counter WizardTM 1470, PerkinElmer to all samples. Biopsies of 3 cm remaining jejunum were removed to histological analyses. Analysis of variance (ANOVA) and the Tukey test for multiple comparisons were used, considering p<0.05 as significant. The study had the participation of some departments and laboratories, as Nucleus of Experimental Surgery, Department of Surgery, Laboratory of Radiobiology, Department of Pathology and Service of Nuclear Medicine, certifying the character of a multidisciplinary research. The results were no significant differences in %ATI/g of the sodium pertechnetate in the organs of the groups studied (p>0.05). An increase in the weight of the SB rats was observed after the second postoperative week. The jejunal mucosal thickness of the SB rats was significantly greater than that of C and sham rats (p<0.05. The biodistribution of sodium pertechnetate was not affected by massive intestinal resection in rats. An adaptive response by the intestinal mucosa probably contributed to the reversion of weight loss and the biodistribution of sodium pertechnetate was not affected by the surgery